Case Report: Nasal Cavity Dermoid Cyst A Rare Presentation and Surgical Excision - S, Vignesh .; G, Radhika.; Dheenadhayalan, M.; Karthickeyan, K.; Shanmugasundaram, P.; Sundar Sri, M. K. (Journal of Neonatal Surgery, 2025)
The patient is a 59-year-old female presenting with nasal obstruction and dysphagia, accompanied by nasal masses upon examination. A dermoid cyst, a rare benign tumor often consisting of various tissues such as skin, hair, or sebaceous material, was diagnosed in the nasal cavity. Dermoid cysts in this region are infrequent, making this case particularly significant to existing medical literature. The clinical suspicion of a dermoid cyst was raised based on the patient's symptoms and confirmed by imaging modalities like CT scans. The patient underwent surgical excision of the cyst, followed by histopathological analysis. Post-surgery, the patient had an uneventful recovery with no signs of recurrence. This case emphasizes the importance of early detection and surgical intervention, leading to a positive prognosis and an improved quality of life without recurrence during follow-up.